2018
DOI: 10.1108/mbr-07-2017-0044
|View full text |Cite
|
Sign up to set email alerts
|

Top management team international experience and strategic decision-making

Abstract: Purpose This study aims to explore the influence of top management team international experience on international strategic decision-making rationality and, subsequently, its effect on decision effectiveness (decision performance). Design/methodology/approach This analysis is based on survey data of small- and medium-sized international Pakistani firms operating in the IT industry. Findings Results show that top management team international experience is positively related to international strategic decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 79 publications
(154 reference statements)
0
14
0
Order By: Relevance
“…However, in the international business literature, this focus on top manager characteristics, the decision-making process and decision rationality is scarce despite its importance for the international strategic decision-making process (Ji and Dimitratos, 2013; Child and Hsieh, 2014; Elbanna et al , 2020). To address this gap, Azam et al (2018) show that the international experience of the TMT is positively associated to international strategic decision rationality and that, in turn, international strategic decision rationality is positively associated to decision effectiveness. Similar to most upper echelons studies, Azam et al (2018) rely on a (logical) proxy (Hambrick, 2007) to represent the two sources of this effect: the direct effect of TMT personal international knowledge and the indirect effect of international information acquired from top managers’ international contacts.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in the international business literature, this focus on top manager characteristics, the decision-making process and decision rationality is scarce despite its importance for the international strategic decision-making process (Ji and Dimitratos, 2013; Child and Hsieh, 2014; Elbanna et al , 2020). To address this gap, Azam et al (2018) show that the international experience of the TMT is positively associated to international strategic decision rationality and that, in turn, international strategic decision rationality is positively associated to decision effectiveness. Similar to most upper echelons studies, Azam et al (2018) rely on a (logical) proxy (Hambrick, 2007) to represent the two sources of this effect: the direct effect of TMT personal international knowledge and the indirect effect of international information acquired from top managers’ international contacts.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…To address this gap, Azam et al (2018) show that the international experience of the TMT is positively associated to international strategic decision rationality and that, in turn, international strategic decision rationality is positively associated to decision effectiveness. Similar to most upper echelons studies, Azam et al (2018) rely on a (logical) proxy (Hambrick, 2007) to represent the two sources of this effect: the direct effect of TMT personal international knowledge and the indirect effect of international information acquired from top managers’ international contacts. They do not explicitly test whether personal international knowledge and international information have separate effects on international strategic decision rationality.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has shown a number of factors that lead to improving the effectiveness of strategic decisions; these factors include the experience level of the management team (Azam et al, 2018), the ability to manage tension and create managerial acceptance of decisions (Calabretta et al, 2017), the ability to minimize the conflict levels and increase the level of collaboration among the organization's members (Hurt and Abebe, 2015), the ability to identify individual differences and exploit motivations (Borrero et al, 2017), and the ability to create shared values, facilitate information exchange, and encourage cooperative behavior (Gu et al, 2016).…”
Section: Consequential: Strategic Decisions Commit Substantial Resourcesmentioning
confidence: 99%